2022
DOI: 10.3389/fcimb.2022.736397
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Microbiome in the Pathogenesis of COVID-19

Abstract: The ongoing pandemic coronavirus disease COVID-19 is caused by the highly contagious single-stranded RNA virus, SARS-coronavirus 2 (SARS-CoV-2), which has a high rate of evolution like other RNA viruses. The first genome sequences of SARS-CoV-2 were available in early 2020. Subsequent whole-genome sequencing revealed that the virus had accumulated several mutations in genes associated with viral replication and pathogenesis. These variants showed enhanced transmissibility and infectivity. Soon after the first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 198 publications
(630 reference statements)
0
18
0
Order By: Relevance
“…Our findings suggest that it is imperative to elucidate all the implications of SARS-CoV-2 infection, especially its effect on the gut microbiome community and functions. Although other studies have involved the severe cases of COVID-19 [7,65,66], none of these studies include both metagenomic and metatranscriptomic sequencing data. We found that the virulence factors and antimicrobial resistance genes were indeed expressed in higher levels in the COVID-19 group compared to the controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings suggest that it is imperative to elucidate all the implications of SARS-CoV-2 infection, especially its effect on the gut microbiome community and functions. Although other studies have involved the severe cases of COVID-19 [7,65,66], none of these studies include both metagenomic and metatranscriptomic sequencing data. We found that the virulence factors and antimicrobial resistance genes were indeed expressed in higher levels in the COVID-19 group compared to the controls.…”
Section: Discussionmentioning
confidence: 99%
“…PathoFact was run on the contigs assembled by IMP together with their predicted protein sequences (ORFs) for each sample separately. PathoFact uses DeepARG [63] and RGI [61] for the prediction of ARGs, DeepVirFinder [64] and VirSorter [65] for the prediction of phages and PlasFlow [66] for the prediction of plasmids. Additionally, PathoFact uses its own developed tool, a combination of a HMM database (built on the VFDB [67]) and a random forest model, for the prediction of virulence factors.…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…However, few studies evaluated the gut microbiota as a prognostic factor for disease progression in hospitalized patients. The existence of a correlation between the COVID-19 severity and fecal microbiota dysbiosis (including depletion of commensal bacteria) has been reported ( De and Dutta, 2022 ). As shown by Zuo et al (2020) , twenty-three bacterial taxa were significantly correlated with disease severity, with the main bacteria belonging to the phylum Firmicutes and the genus Coprobacillus , as well as the Clostridium ramosum and Clostridium hathewayi species.…”
Section: Discussionmentioning
confidence: 98%
“…HSA is known to act as a receptacle in protecting bacterial microbiomes [9]. A microbiome formation is possible between COVID-19 virions [10]. Due to the long halflife of HSA both in the interstitial spaces and the body any bound COVID-19 virions therefore may be trapped for weeks or months.…”
Section: Long Covid-19mentioning
confidence: 99%